1997
DOI: 10.1159/000134525
|View full text |Cite
|
Sign up to set email alerts
|

Mapping in pig of genes involved in sexual differentiation: AMH, WT1 FTZF1, SOX2, SOX9, AHC, and placental and embryonic CYP19

Abstract: Intersexuality has been reported in pigs and investigations are in progress to identify and physically map the genes involved in sex-reversal. In this study we have mapped on porcine chromosomes seven genes which might be implicated in this developmental pathway. Four genes were mapped by radioactive in situ hybridization: AMH (Anti-Müllerian Hormone) and WT1 (Wilms’ Tumor gene 1) were both mapped to pig chromosome 2 (SSC2) in the q14→q21 and p14→q11 regions, placental CYP19 (cytochrome P450, subfamily XIX) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It might thus be possible that AromP450 isozyme, which is distinct from that in the mPOAM and derived from a different gene, is expressed in the young‐to‐adult type of areas. The presence of AromP450 isozymes has already been reported for pigs (Choi et al,1997; Conley et al,1997; Lahbib‐Mansais et al,1997) and fishes (Kitawaki et al,1987; Osawa et al,1987; Callard and Tchoudakova,1997; Tchoudakova and Callard,1998). For the zebra finch, it has been suggested that two types of aromatase in the hypothalamus and telencephalon are distinctive in biochemistry and in hormonal regulation (Balthazart et al,1990).…”
Section: Discussionmentioning
confidence: 76%
“…It might thus be possible that AromP450 isozyme, which is distinct from that in the mPOAM and derived from a different gene, is expressed in the young‐to‐adult type of areas. The presence of AromP450 isozymes has already been reported for pigs (Choi et al,1997; Conley et al,1997; Lahbib‐Mansais et al,1997) and fishes (Kitawaki et al,1987; Osawa et al,1987; Callard and Tchoudakova,1997; Tchoudakova and Callard,1998). For the zebra finch, it has been suggested that two types of aromatase in the hypothalamus and telencephalon are distinctive in biochemistry and in hormonal regulation (Balthazart et al,1990).…”
Section: Discussionmentioning
confidence: 76%
“…It might thus be possible that AromP450 isozyme, which is distinct from that in the mPOAM and derived from a different gene, is expressed in the young-to-adult type of areas. The presence of AromP450 isozymes has already been reported for pigs (Choi et al, 1997;Conley et al, 1997;Lahbib-Mansais et al, 1997) and fishes Osawa et al, 1987;Callard and Tchoudakova, 1997;Tchoudakova and Callard, 1998). For the zebra finch, it has been suggested that two types of aromatase in the hypothalamus and telencephalon are distinctive in biochemistry and in hormonal regulation (Balthazart et al, 1990).…”
Section: Distinct Characteristics Of Young-to-adult Group Aromatasementioning
confidence: 87%
“…We further analyzed the YB-1 localization in different rat glomerular disease models, including immunologic injury to podocytes (PHN), toxic injury to podocytes (PAN), spontaneous normotensive nephrosclerosis (38), and diabetic Zucker rats. Despite the presence of significant glomerular injury in all of these models, YB-1 remained localized predominantly to cell nuclei within the glomerular, tubulointerstitial, and vascular compartment, comparable to healthy control animals ( Figure 3).…”
Section: Yb-1 Localization In Glomerular Disease Modelsmentioning
confidence: 99%